Sustainable Tourism Development Through Endogenous Growth Models - Dimitrios Lagos; Eleni Stamatiou (European Regional Science Association (ERSA), 2006)
The effective comprehension of mechanisms of achievement of sustainable tourism development presupposes the existence of standardised models. Endogenous development models constitute decisive factor for the development of theoretical discoveries and in the tourism activity. The modern bibliography provides usually inaccurate criteria of sustainability, mainly because of the restrictive standardisation of environmental components. This fact influences considerably the choice of policies, because in certain cases it is likely that dilemmas of the environment or development will present themselves. Moreover, the importance of the consuming behaviour of tourists tends to be neglected in the effort of finding ecological ways of development, even though this analysis allows the discovery of new tools of tourism policy for public organizations. In the frame of the above reflection with this proposal is targeted the critical research of the possibility of integration, but also the way of incorporation of sustainable tourism development in the various models of endogenous development. In the theoretical analysis of this subject, the detailed description of various endogenous models of development will be sought. Then, will be examined the importance of sustainable tourism development and the necessity for its integration in the endogenous development models. Immediately next, will be examined critically the functional incorporation of the tourism activity in each model of endogenous development and will be underlined the importance that it has on tourism policy.
Keywords: 330